Gender, work, and medicine : women and the medical division of labour - Riska, Elianne; Riska, Elianne; Wegar, Katarina (London ; Newbury Park, Calif. : Sage Publications, 1993)
Gender, Work and Medicine provides a critical assessment of the division of labour in medicine, setting current practice in its historical context. The book demonstrates the centrality of gender divisions both between and within the individual medical and health professions - doctors, nurses, midwives and others."--BOOK JACKET. "Drawing on accounts from different countries and a wide range of professional groups, the contributors examine the extent to which the division of labour is changing and the effect of such changes on the status of women within the health professions. While the proportion of female doctors is rising, the continued constraints on women attaining full equality are explored."--BOOK JACKET. "This broad-ranging book will be invaluable reading for students and lecturers in the medical and health professions and in medical sociology and the sociology of the professions."--BOOK JACKET
Keywords: Medical care; Women in medicine; Social medicine